Personality traits, self-employment, and professions - Michael Fritsch; Alina Rusakova (Friedrich Schiller University Jena and Max Planck Institute of Economics, 2010)
We investigate the effect of broad personality traits' - the Big Five - on an individua's decision to become self-employed. In particular, we test an overall indicator of the entrepreneurial personality. Since we find that the level of self-employment varies considerably across professions, we also perform the analysis for different types of professions, namely, those classified as being in the 'creative class' as compared to the noncreative class. The analysis is based on micro data for individuals of the German Socio Economic Panel (SOEP). We find a significant association between personality traits and the propensity be become self-employed. However, the strength of this link is fairly weak and differs across professions, indicating an important effect of an individual's profession on his or her decision to run an own business.
Keywords: L26; Z1; D03; 330; entrepreneurship; self-employment; personality traits; the Big Five; professions; Selbstständige; Unternehmensgründung; Persönlichkeitspsychologie; Beruf; Schätzung; Deutschland